Undergraduate medical education. Issue 6872 (23rd January 1993) - Rees, L; Wass, J
Abstract : Pressures from students and teachers, from professional bodies, and from changes in the way health care is delivered are all forcing a rethink of how medical students should be taught. These pressures may be more intense in London but are not confined to it. The recommendation the Tomlinson report advocates that has been generally welcomed is for more investment in primary care in London. General practitioners have much to teach medical schools about effective ways of learning, but incentives for teaching students in general practice are currently low, organising such teaching is difficult and needs resources, and resistance within traditional medical school hierarchies needs to be overcome. Likewise, students value learning within local communities, but the effort demanded of public health departments and community organisations is great at a time when they are under greater pressure than ever before. The arguments over research that favour concentration in four multifaculty schools are less clear cut for undergraduate education, where personal support for students is important. An immediate concern is that the effort demanded for reorganising along the lines suggested by Tomlinson will not leave medical schools much energy for innovating.